Is aspiration an effective acute stroke treatment in older adults? - Narloch, Jerzy; Piasecki, Adam; Ziecina, Piotr; Dȩbiec, Aleksander; Wierzbicki, Marek; Staszewski, Jacek; Piasecki, Piotr (Frontiers in Neurology, 2023)
Introduction Clinical outcomes after interventional stroke treatment rely on several factors, with older age being associated with poorer results, which are mainly attributed to patient's comorbidities and medications. The delivery of an aspiration catheter could be hindered by carotid tortuosity, which is more prevalent in elderly patients with increasing age. In this study, we aimed to compare the clinical and angiographic outcomes of a direct aspiration first-pass technique in interventional stroke treatment for elderly patients compared with younger patients. Materials and methods A total of 162 patients (92 women and 70 men, aged between 35 and 94 years +/– 12.4 years) were included in this study. Patients who were treated in a comprehensive stroke center due to a large-vessel occlusion stroke using aspiration as the first-choice treatment were included in this study. To evaluate carotid arteries, the tortuosity index (TI) was calculated for each segment of each carotid pathway. Results Age correlated significantly with the presence of carotid tortuosity (R = 0.408, p = 0.000), extracranial length ratio (R = 0.487, p = 0.000), and overall length ratio (R = 0.467, p = 0.000). No significant associations were found with coiling, kinking, or intracranial length ratio. Successful aspiration-based recanalization rate decreased with increasing age, and the differences between the age subgroups were not statistically significant. A comparison of the extreme subgroups, i.e., <60 years old vs. ≥80 years old, did not yield a statistically significant change (p = 0.068). Conclusion Successful aspiration-based recanalization rate decreased with increasing age; however, these differences were not significant. Clinical outcomes did not significantly differ with regard to carotid tortuosity, regardless of the time of assessment. Neither intracranial nor extracranial tortuosity was significantly associated with reperfusion-related complications in either of the age subgroups.